Paleoflora de la Formación Paraná (Mioceno Tardío), Cuenca Chaco-Paranense, Argentina. - Brea, Mariana (2013)
El Neógeno de la Mesopotamia argentina. D.Brandoni y J.I.Noriega, Editores (2013) Asociación Paleontológica Argentina, Publicación Especial 14: 22?34 The fossil record of the palm phytolith affinity with Trithrinax Mart. and Copernicia Mart. ex Endl., foliar impression affinity with Ocotea Aublet., Paramyrciaria Kausel and Schinus L. and wood fossils with linked to Anadenanthera Speg., Parapiptadenia Brenan, Astronium Jack. and Solanum L. in the late Miocene from the Paraná Formation, support the idea that these elements were more widespread in the past and would indicate a warmer and more humid climate than at present in this region. The presence of Anadenantheroxylon villaurquisense Brea, Aceñolaza and Zucol, 2001, and Astroniumxylon portmanii Brea, Aceñolaza and Zucol, 2001, two wood fossils showing affinity with Anadenanthera colubrina var. cebil (Vell.) Brenan and Astronium urundeuva (Fr. Allem.) Engl respectively, suggest that Seasonally Dry Tropical Forests covering a wider area further south during the Miocene.